A GESTÃO DA POLÍTICA EDUCACIONAL NO COTIDIANO DA ESCOLA: perspectiva democrática da atuação do conselho escolar no município de São Luís-MA - Campos, Nadja Fonseca da Silva Cutrim (2011)
This dissertation entitled The Management of Educational Policy in everyday school: a democratic role of the school board in the municipal schools in São Luís-MA, is in line State Research and Educational Management, and Research Group Basic Education Policy Program Graduate Education at the Federal University of Maranhão. The overall objective of this study is to analyze the design of (de) centralization of management of educational policy and the principles of democratization of school management. Investigates the Brazilian educational scenario from the 1990s, the focus of analysis focusing on the reform of state administration and its implications for educational policy in a context of implementation of neoliberal ideology. We analyzed the policy that guided the deployment and operation of school councils in the Municipality of São Luís-MA, during 2002-2008, from the perspective of managers of both the City Department of Education as school managers and members of the Council School Regarding the methodology applied in this study is characterized as qualitative research, whose methodological approach was developed linking bibliographic and documental research and field trials. In this sense we sought to theoretical basis of the contributions of Ghedin, 2008; Bardin, 1977; Bordignon and Grace, 2001; Paro, 2002; Gohn, 2001; Cury, 2004; Gadotti, 2001; Barroso, 2003; Luck, 2006; Ferreira , 2000; Werle, 2003; Foucault, 1981, among others about the concepts of management and exercise of power and how historically been configured to replace the design of democratic management by the school administration. Data collection script was used semi-structured interviews with 03 managers applied the Municipal Education Secretariat of Sao Luis, 01, and managing the school studied, 04 members of the School Board representatives segments of parents, students, staff and faculty. Sought to understand the guidelines and policy developments central SEMED in school management and its implications of the School Board, especially after the implantation of the St. Louis, Te I Reading and Writing, which occurs when a "reconfiguration "instance of this power. It was evident that the democratic administration and school board have a prominent place in current education policies, are present in various propositions presented by the Brazilian government as key to achieving the goals of education reform. We identified the managerial character of the conception of democratic management, arising from the design business, while taking a contradictory view of democratization, expressing the standard prescriptive and normative official speeches whose purpose is the decentralization of responsibilities and power concentration. However, we conjecture that, although the reform is a concept forged marketing education, in which power relations are strengthened, it can also be found elements that provide a different perspective of school that is truly democratic, and that triggers participation processes required for recognition while building a new social quality management from the perspective of educational policy in the city of St. Louis